Enhancing MSME Competitiveness Through Packaging Logo Design In Marlempang Village - Nuraida Nuraida; Sayed Ahmad Zaki Yamani; Rahmawati Rahmawati; Munar Akram; Nailus Saadah; Raihan Fitriani; Reva Auzira; Zita Rizkia; Cut Aliani; Suci Nazilatul Aini (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Marlempang Village have great potential in the field of local processed food products. Unfortunately, most MSME actors do not yet have the ability to utilize visual elements of products such as logo and packaging design. In fact, logos and packaging are important aspects in building brand identity, attracting consumer attention, and increasing the selling value and competitiveness of products. This community service activity aims to increase the competitiveness of MSMEs by providing training in designing logos and packaging that are attractive, functional, and in accordance with the character of the product. The implementation method includes counseling on the importance of visual design, training in making logos and packaging with simple design applications (Canva), and direct assistance for each MSME. The results of the activity showed an increase in MSME actors' understanding of the importance of visual identity and the ability to design logos and product packaging. It is hoped that this activity will contribute to increasing sales and branding of local products in Marlempang Village. With this assistance, MSMEs in Marlempang Village have a greater opportunity to develop sustainably. This activity has a positive impact on the branding and competitiveness of local MSME products. Further recommendations are digital marketing training and product legality assistance to increase business scale.